Childhood allergy disease, early diagnosis, and the potential of salivary protein biomarkers - Mohamad Zainal, Nurul Hayati; Abas Buang, Razif; Mohamad Asri, Siti Fadziyah (Hindawi Publishing, 2021)
Allergic disease has risen to epidemic proportions since the last decade and is among the most common noncommunicable, chronic diseases in children and adolescents worldwide. Allergic disease usually occurs in early life; thus, early biomarkers of allergic susceptibility are required for preventive measures to high-risk infants which enable early interventions to decrease allergic severity. However, to date, there is no reliable general or specific allergy phenotype detection method that is easy and noninvasive for children. Most reported allergic phenotype detection methods are invasive, such as the skin prick test (SPT), oral food challenge (OFC), and blood test, and many involve not readily accessible biological samples, such as cord blood (CB), maternal blood, or newborn vernix. Saliva is a biological sample that has great potential as a biomarker measurement as it consists of an abundance of biomarkers, such as genetic material and proteins. It is easily accessible, noninvasive, collected via a painless procedure, and an easy bedside screening for real-time measurement of the ongoing human physiological system. All these advantages emphasise saliva as a very promising diagnostic candidate for the detection and monitoring of disease biomarkers, especially in children. Furthermore, protein biomarkers have the advantages as modifiable influencing factors rather than genetic and epigenetic factors that are mostly nonmodifiable factors for allergic disease susceptibility in childhood. Saliva has great potential to replace serum as a biological fluid biomarker in diagnosing clinical allergy. However, to date, saliva is not considered as an established medically acceptable biomarker. This review considers whether the saliva could be suitable biological samples for early detection of allergic risk. Such tools may be used as justification for targeted interventions in early childhood for disease prevention and assisting in reducing morbidity and mortality caused by childhood allergy.